DEVELOPER AND ADMINISTRATOR MAP OF THE CLINICAL DEPARTMENT SITE OF THE HIGHER EDUCATIONAL MEDICAL INSTITUTION - Lopina, Н.А.; Zhuravlova, Л.В. (Journal of Information Technologies in Education (ITE), 2018)
Currently, medicine is one of the most dynamically developing areas of knowledge. Modern medical education is characterized by its continuity, dynamism, which ensures the professional competence of the doctor throughout his professional career. Every year, new data accumulates in one or another area of medical knowledge, a large number of clinical studies are conducted, and clinical guidelines for the diagnosis and treatment of different pathologies are reprinted. Medical professionals need high-quality educational information content, available to the doctor in their workplace. To implement a continuous educational process in medical education, the clinical departments of higher educational institutions can create an informational web-space with high-quality information and educational content called web sites. However, not always the members of the team of the developers of information content of the sites of the clinical departments of educational institutions (it-specialists, medical teachers and practicing doctors) interact productively enough with each other and understand the educational goals, tasks, prospects. Due to our own experience in developing and implementing the clinical department of the information web space in the educational process, we offer a detailed sequential map-algorithm that can be used in the development and administration of the site by the clinical departments of a higher educational medical institution that can combine all members of the educational sites developers team.